Does Profitability, Firm Size, And Investment Opportunity Set Affect Earnings Quality? - Budi Andriani; Mahfud Nurnajamuddin; Khairina Rosyadah (Jurnal Akuntansi, 2021)
This paper examines the relative importance of firm size, investment opportunity set, and probability in predicting earnings quality. This study's research method involves using quantitative data. The purpose of this study is to analyze companies in Indonesia that publish financial reports and disseminate them on the Indonesia Stock Exchange. The study population is the financial statements of manufacturing companies in the consumer goods industry sector that are listed on the IDX as many as 50 companies with purposive sampling technique so that it becomes 38 company financial reports with two years of data so that the total sample to 76 financial statement data. The data collected from the Indonesian stock exchange were analyzed by multiple regression using ordinary least squares with the Eviews software (V.11). The results of the study show that profitability, size, and investment opportunity are positively correlated with higher-quality earnings. Consequently, the company's profitability has a positive and significant effect on its financial performance, meaning that the more profitable a company, the stronger its earnings. Company size is positively affected by the earnings quality of a company, meaning that larger companies reward higher quality earnings. The investment opportunity set has a positive and significant effect on earnings quality, which means that earnings quality increases because more investors are interested in investing.